2019
DOI: 10.1002/pds.4908
|View full text |Cite
|
Sign up to set email alerts
|

Understanding utilization patterns of biologics and biosimilars in the United States to support postmarketing studies of safety and effectiveness

Abstract: Purpose: To describe utilization of filgrastim and infliximab, the first two products with biosimilars approved in the United States. Methods: We identified use of filgrastim (reference, tbo-filgrastim, and filgrastimsndz) and infliximab (reference, infliximab-dyyb, and infliximab-abda) in the Sentinel Distributed Database using Healthcare Common Procedure Coding System (HCPCS) codes and National Drug Codes (NDCs) from January 2015 to August 2018. We calculated the proportion of use by code type and assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…17 A recent study using the FDA Sentinel Distributed Database found that filgrastim-sndz's use had increased to 49.3% by August 2018. 18 Similarly, Karaca-Mandic et al also confirmed similar uptake among the commercially insured and Medicare Advantage populations. 19 In addition, Socal et al used the 2015-2017 Medicare Part B claims data and found an improved uptake of biosimilar filgrastim in the Medicare Part B program.…”
Section: What This Study Addsmentioning
confidence: 80%
See 1 more Smart Citation
“…17 A recent study using the FDA Sentinel Distributed Database found that filgrastim-sndz's use had increased to 49.3% by August 2018. 18 Similarly, Karaca-Mandic et al also confirmed similar uptake among the commercially insured and Medicare Advantage populations. 19 In addition, Socal et al used the 2015-2017 Medicare Part B claims data and found an improved uptake of biosimilar filgrastim in the Medicare Part B program.…”
Section: What This Study Addsmentioning
confidence: 80%
“…Findings from the current study could fill the important knowledge gap in the uptake and spending of biosimilar filgrastim in national populations, especially Medicare feefor-service beneficiaries with Part D prescription coverage and Medicaid beneficiaries. Although the Dutcher et al study described the use of biosimilar filgrastim-sndz at the national level, using the FDA's Sentinel Distributed Database, 18 no findings in cost or spending of the product were reported.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Little is known about the impact and uptake of this device and approved biosimilars on G-CSF prescribing patterns and the uptake of these new products in the United States. Existing studies evaluated utilization at the prescription level rather than patient level, 16 , 17 , 18 , 19 , 20 , 21 limiting insights into trends within certain patient groups, for example, those with high FN risk owing to regimen or patient factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, biosimilars have been underutilized 15 despite multiple position statements from societal organizations supporting their use in IBD management 12,13 and medical evidence supporting their safety and efficacy. [8][9][10][11] Biosimilars have seen a minimal increase in market share from 0.1% in 2017 to 0.9% in 2019.…”
Section: Discussionmentioning
confidence: 99%